The integrative model for the semantic space of music and a contemporary musical educational process: the scientific and creative heritage of Mikhail Borisovich Ignatyev - Irina Gorbunova (Universidade Federal de Santa Maria, 2021)
The advent of computer technology has led to the creation and development of new forms of teaching musical art. The emergence of music computer technologies (MCT) was the basis for creating both new forms in the educational process and new subjects, the appearance of new disciplines and new educational trends in the system of a contemporary musical education. These new subjects, such as "Musical Informatics," "Computer Music Creative Work," "Computer Arrangement and Composition, Sound and Timbre Programming," "Electronic Musical Instruments" and many others, fully reflect the essence of the changes that have occurred in approaches to the study of music art. This article analyzes the possibility of including an integrative model for the semantic space of music, developed with the participation of the prominent cybernetics, scientist Mikhail Borisovich Ignatyev, in a contemporary musical educational process.